Comparative Study of Concrete Strength by Partial Replacing of Coarse Aggregate with Crushed Tiles and Sea Shell - Deepapriya, S.; kumar, Pappu; Srivastava, Nihal (International Journal of Engineering and Technology, 2018)
Concrete is a very important component of construction material which is used in all country. This importance has created a huge demand for concrete manufacture. Henceforth the cost of concrete is also increasing nowadays. Because of this condition the construction has become very expensive. This coupled with harmful consequence of concrete manufacture on the environment lead to studies on various materials which could be used as partial replacement for coarse aggregate. This has necessitated investigate into optional materials of construction and analysing the compressive behaviour and split tensile strength of the concrete which was designed by partial replacement of the coarse aggregates by construction tiles waste and sea shell. For this research, M25 Grade of concrete was selected. The comparative study of strength obtained by the mix design by varying the replacement ratios of coarse aggregate by sea shell and construction tile waste was also done. Fine aggregate and coarse aggregates samples are sieved and the sample required is selected accordingly. Specific gravity test is done for fine and coarse aggregate. In our project Design mix use for M25 grade for using 1:1:2 with ratio 0.50.The crushed tiles and seashell were cast the cube test for slump test and compressive strength and we tested in the interval of 7 days ,14 days and 28 days.